Alterations in the in vitro and in vivo regulation of muscle regeneration in healthy ageing and the influence of sarcopenia. Issue 1 (6th December 2017) - Brzeszczyńska, Joanna; Meyer, Angelika; McGregor, Robin; Schilb, Alain; Degen, Simone; Tadini, Valentina; Johns, Neil; Langen, Ramon; Schols, Annemie; Glass, David J.; Roubenoff, Ronenn; Ross, James A.; et al.
Abstract: Background: Sarcopenia is defined as the age‐related loss of skeletal muscle mass and function. While all humans lose muscle with age, 2–5% of elderly adults develop functional consequences (disabilities). The aim of this study was to investigate muscle myogenesis in healthy elderly adults, with or without sarcopenia, compared with middle‐aged controls using both in vivo and in vitro approaches to explore potential biomarker or causative molecular pathways associated with sarcopenic versus non‐sarcopenic skeletal muscle phenotypes during ageing. Methods: Biomarkers of multiple molecular pathways associated with muscle regeneration were analysed using quantitative polymerase chain reaction in quadriceps muscle samples obtained from healthy elderly sarcopenic (HSE, n  = 7) or non‐sarcopenic (HENS, n  = 21) and healthy middle‐aged control (HMC, n  = 22) groups. An in vitro system of myogenesis (using myoblasts from human donors aged 17–83 years) was used to mimic the environmental challenges of muscle regeneration over time. Results: The muscle biopsies showed evidence of satellite cell activation in HENS (Pax3, P  < 0.01, Pax7, P  < 0.0001) compared with HMC. Early myogenesis markers Myogenic Differentiation 1 (MyoD1) and Myogenic factor 5 (Myf5) ( P  < 0.0001) and the late myogenesis marker myogenin (MyoG) ( P  < 0.01) were increased in HENS. In addition, there was a 30‐fold upregulation of TNF‐α in HENS compared with HMC ( P  < 0.0001). The in vitro system demonstrated age‐related upregulation of pro‐inflammatory cytokines (2‐fold upregulation of interleukin (IL)‐6, IL‐8 mRNA, increased secretion of tumor necrosis factor‐α (TNF‐α) and IL‐6, all P  < 0.05) associated with impaired kinetics of myotube differentiation. The HSE biopsy samples showed satellite cell activation (Pax7, P  < 0.05) compared with HMC. However, no significant upregulation of the early myogenesis (MyoD and Myf5) markers was evident; only the late myogenesis marker myogenin was upregulated ( P  < 0.05). Higher activation of the oxidative stress pathway was found in HENS compared with the HSE group. In contrast, there was 10‐fold higher upregulation of HSPA1A a stress‐induced chaperone acting upon misfolded proteins in HSE compared with the HENS group. Conclusions: Both pathological and adaptive processes are active in skeletal muscle during healthy ageing. Muscle regeneration pathways are activated during healthy ageing, but there is evidence of dysregulation in sarcopenia. In addition, increased cellular stress, with an impaired oxidative‐stress and mis‐folded protein response (HSPA1A), may be associated with the development of sarcopenia. The in vitro system of young and old myoblasts replicated some of the differences between young and old muscle.